PENGARUH JUMLAH BLADE DAN VARIASI PANJANG CHORD TERHADAP PERFORMANSI TURBIN ANGIN SUMBU HORIZONTAL (TASH) - Wiratama, I Kade; Mara, Made; Furqan Prina, L. Edsona (Universitas Mataram, 2014)
The willingness of electrical energy is one energy system has a very important role in the economic development of a country's survival. As one energy source (wind) can be converted into electrical energy with the use of a horizontal axis wind turbine. Wind Energy Conversion Systems (WECS) that we know are two wind turbines in general, ie the horizontal axis wind turbine and vertical axis wind turbine is one type of renewable energy use wind as an energy generator. The purpose of this study was to determine the effect of the number of blade and the radius chord of rotation (n), Torque (T), Turbine Power (P), Power Coefficient (CP) and Tip Speed Ratio (λ) generated by the horizontal axis wind turbine with form linear taper. The results show that by at the maximum radius of the chord R3 the number blade 4 is at rotation = 302.700 rpm, Pturbine = 7.765 watt, Torque = 0.245 Nm, λ = 3.168 and Cp = 0.403 or 40.3%.